2022
DOI: 10.3390/brainsci12020190
|View full text |Cite
|
Sign up to set email alerts
|

A Peek into Pandora’s Box: COVID-19 and Neurodegeneration

Abstract: Ever since it was first reported in Wuhan, China, the coronavirus-induced disease of 2019 (COVID-19) has become an enigma of sorts with ever expanding reports of direct and indirect effects of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on almost all the vital organ systems. Along with inciting acute pulmonary complications, the virus attacks the cardiac, renal, hepatic, and gastrointestinal systems as well as the central nervous system (CNS). The person-to-person variability in susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 293 publications
(231 reference statements)
1
20
0
Order By: Relevance
“…Given the mechanisms described so far and their inevitable neuronal degeneration and necrosis spectrum of sequelae, they are predominantly the ones occurring in severe and fatal cases [26,68,89]. Accumulating evidence suggests additional mechanisms associated with SARS-CoV-2 infection that could trigger or accelerate already-developed neurodegenerative disorders [117,118].…”
Section: Neurodegenerationmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the mechanisms described so far and their inevitable neuronal degeneration and necrosis spectrum of sequelae, they are predominantly the ones occurring in severe and fatal cases [26,68,89]. Accumulating evidence suggests additional mechanisms associated with SARS-CoV-2 infection that could trigger or accelerate already-developed neurodegenerative disorders [117,118].…”
Section: Neurodegenerationmentioning
confidence: 99%
“…Some studies suggest that the viral surface structure acts as a binding site for heparin and accelerates the aggregation and displacement of heparin-binding proteins such as Aβ, α-synuclein, tau, prion, and TDP-43 RRM, resulting in initiation or acceleration of the associated neurodegenerative pathways [119,120]. Other studies have also suggested that within the host cells, the SARS-CoV-2 viral protein interacts with multiple intracellular pathways associated with aging, taking part in vesicle trafficking, lipid modifications, RNA processing and regulation, ubiquitin ligases, and mitochondrial activity, while at the same time depleting intracellular iron and further hindering mitochondrial function [59,60,117]. Furthermore, as the virus enters the host cell through the ACE-2 receptor, viral interaction may lead to decreased functionality, reducing the neuroprotective effects of ACE-2 [121,122].…”
Section: Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence suggest that the neurological aspects of long COVID may point toward degeneration of neural targets [ 215 ]. ACE implication may be of interest because SARS-CoV-2 infection can impair the disassembly of host stress granules (SGs) and promote the aggregation of SG-related amyloid proteins, which may lead to an increased risk of neurodegeneration [ 216 ].…”
Section: Renin-angiotensin-aldosterone System and Prion Diseasementioning
confidence: 99%